A Qualitative Exploration of Collective Collapse in a Norwegian Qualifying Premier League Soccer Match—The Successful Team's Perspective - Schei, Gaute S.; Haugen, Tommy; Jones, Gareth; Sæther, Stig Arve; Høigaard, Rune (Frontiers in Psychology, 2022)
The current case study focused on a crucial match in the qualification for the Norwegian Premier League (Eliteserien). In the match, the participants of the study experienced a radical change in performance toward the end of the second half, from being behind by several goals to scoring 3 goals in 6 min and winning the qualifying game. The purpose of this study was therefore to examine the perceptions and reflections of players and coaches (sporting director) on what occurred within their own team and within the opposing team. The momentum shift in the opposition team can be described as a collective collapse. In the study, the theoretical collective collapse process model was used as a guide for the design of the interview questions where five semi-structured interviews were conducted with participants involved in the match (players, coach, and sporting director). The participants watched excerpt clips from the match to recall the main events, which they subsequently reflected on. The results highlighted the importance of the “before-game” aspects (i.e., pressure, first game result), the “during-the-game” behavior (i.e., goals scored, playing with a low degree of risk) and the cognitive (i.e., feelings of pressure, despair) and emotional reactions (i.e., frustration, joy) to the match unfolding. In addition, social contagion processes were evident in both teams relating to emotion and behavior. Overall, the data from this study investigated the general structure of the process model of collective sport team collapse and found support for the notion of a temporal cascade of causes for a team collapse. Future research is encouraged to examine this model, to provide guidance to teams, coaches, and sport psychologists in order to make recommendations for dealing with collective collapse in sport teams.